Arteria lusoria dissection with mediastinal hematoma as a complication of a transradial coronary catheterization: Case report and literature review. (2020) - Serra, Raffaele; Rocca, Tiberio; Traina, Luca; Licastro, Noemi; Ielapi, Nicola; Gasbarro, Vincenzo
Highlights: Aberrant right subclavian artery (ARSA), or arteria lusoria is the most common embrologic anomaly of the aortic arch. The ARSA arises after the origin of the left subclavian artery and then reaches the posterior mediastinum. The presence of ARSA is generally asymptomatic, but may cause complications, during some endovascular procedures. Prompt diagnosis and treatment is required to avoid more dreadful complications. Abstract: Introduction: Aberrant right subclavian artery (ARSA), or arteria lusoria is the most common embrologic anomaly of the aortic arch. It is generally asymptomatic and incidentally diagnosed during a radiological exam or procedure. Presentation of case: Here, we report a case of ARSA incidentally diagnosed and injured (dissection with mediastinal hematoma) during a right transradial coronary angiography in a 83 years old female patient. The patient underwent prompt hybrid procedure with the isolation of the right humeral artery from where we positioned a GORE® VIABAHN® 9 × 100 mm endoprosthesis. The procedure was successful with optimal results at early and long term follow up. Discussion: Sometimes, a dissection of the ARSA may occur, especially for excessive manipulation during endovascular procedures, and when such complication happens it should be promptly treated as it can be life-threatening. Conclusion: If transradial catheterization during coronary angiography becomes particularly difficult, requires longer time, or the guide wire enters in the descending aorta, particularly attention should be paid, as dreadful complications such as dissection or lesion may happen and prompt treatment is required.